Processing and Characterization of a Copper Based Binary Alloy Achieved by Solid Phase Compaction and Sintering - Arar, Karim; Mansouri, Salah; Benbouta, Rachid; Fedaoui, Kamel (International Journal of Engineering Research in Africa, 2018)
In the present work, (Cu-Sn, Cu-Co) based alloys with different compositions have been obtained by using powder metallurgy (PM). These alloys were created with the purpose of increasing mechanical and structural properties of the industrial parts. The compacts are made according to the sintering manufacturing method, the uniaxial compressed cold samples. Metallographic characterizations, hardness and density measurements were carried out in order to study the influence of the addition of tin and cobalt, the variation of the compaction pressure and the sintering temperature on the finishing product. It has been proved that the addition of tin and cobalt to a copper powder mixture increase the properties of the sintered parts.